The Effect of Drying Time on the Physicochemical Characteristics of Beetroot (Beta Vulgaris L.) Sheet Jam - Dwi Siska Amanda; Rahmadhia, Safinta Nurindra (JST (Jurnal Sains dan Teknologi), 2024)
The sheet jam from beetroot is a modification of spreadable jam and a diversification of food based on beetroot. Drying is one of the factors that determines the characteristics of the sheet jam. The objective of this study is to determine the effect of drying duration on the physicochemical characteristics of beetroot sheet jam. The drying process was conducted at a temperature of 50 °C with varying drying times of 10, 12, and 14 hours. The analyses performed in this study included texture tests (Hardness, Cohesiveness, Adhesiveness, Gumminess, and Chewiness), pH, moisture content, and antioxidant activity, with three repetitions for each test. The results showed that for the texture parameter, Hardness ranged from 12.66 to 17.65 N, Cohesiveness from 291.76 to 581.04 N, Adhesiveness from 7.35 to 33.58 Nmm, Gumminess from 5198.15 to 7973.70 N, Chewiness from 5117.80 to 7151.6 N, pH ranged from 3.93 to 5, moisture content from 18.85% to 24.95%, and antioxidant activity (IC50) ranged from 38.81 to 47.82 ppm. The conclusion of this study is that drying significantly affects the physicochemical characteristics of beetroot sheet jam.